Pregabalin Prescription for Neuropathic Pain and Fibromyalgia: A Descriptive Study Using Administrative Database in Japan - Mikito Hirakata; Satomi Yoshida; Sachiko Tanaka-Mizuno; Aki Kuwauchi; Koji Kawakami (Pain Research and Management)
Objective. To assess dose, characteristics, and coprescribed analgesics in patients newly prescribed pregabalin for neuropathic pain and fibromyalgia in Japan. Methods. Based on the medical and prescription information present in the Medical Data Vision database, we analyzed the initial and maximum daily doses, prescription period, coprescribed analgesics, and neuropathic pain-related disorders of patients newly prescribed pregabalin between 01 July 2010 and 31 December 2013. Results. A total of 45,331 patients (mean age 66.8 years, 48.7% men) were newly prescribed pregabalin during this period. The mean initial and maximum daily doses were 97.3 mg and 127.8 mg, respectively, and decreased yearly. The duration of the prescription period was 111.9 (mean) and 53 (median) days, and the frequently coprescribed analgesics included NSAIDs, opioids, and Neurotropin®. About one half of the patients had spinal disorders. Conclusion. In Japan during the period examined, the number of newly prescribed pregabalin users increased, but the initial and maximum daily doses decreased yearly after pregabalin went on the market. The maximum daily dose in Japan was lower than those reported in the USA and Europe. These differences might be associated with patient age and physical status and with anxiety about possible adverse events.